Rekonseptualisasi Penyelesaian Perselisihan Hasil Pemilihan Umum di Indonesia - Jayus Jayus (The Constitutional Court of the Republic of Indonesia, 2016)
Elections are the means to implement sovereignty of the people in order to elect members of the House of Representatives, Regional Representatives Council, Local Legislative Council, the President and Vice President. Election are also meaningful for selecting the leader of the nation and the state (public officials) and as community control over board membership, President and Vice President to come. Election results are manifestation of popular sovereignty, which can lead to a dispute between organizer and election participants either political parties or individuals. The result of which can be challenged legally by election participant. The participant can also request the cancellation of the election result to the agency given with the authority to decide. Conceptually, the right institution to decide on election dispute is a special ad hoc election court. Constitutionally, dispute resolution of election result is intended to protect citizens' constitutional rights.